The Value of Moral Reasoning in Whistleblowing: A Milennal Generation Perspective - Wulan, Mulyaning; Niwon Nai, Surya; Arthamevia, Azzura Kania; Fafilla Tiarany, Jihan; Ristira, Sarah (Neo Journal of economy and social humanities, 2022)
Whistleblowingis an action to report fraud or violations committed by a party within the organization. This study aims to examine moral reasoning regarding whistleblowing intentions. This study uses primary data with quantitative methods using questionnaire techniques. The population in this study is the millennial generation aged 25 to 40 years. The hypothesis in this study uses the Partial Least Square (PLS) application. The results of this study state that moral reasoning has a positive effect on the millennial generation's intention to do whistleblowing.